2005
DOI: 10.1002/app.21711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vulcanizing system on the crosslink density of nitrile rubber compounds

Abstract: ABSTRACT:The synergistic activity of binary accelerator systems in rubber vulcanization is well known. Binary accelerator systems are being widely used in industry and are becoming increasingly popular because of the fact that such mixed systems can produce a vulcanizate with superior mechanical properties compared to those of stock cured with a single accelerator. The authors have studied the performance of a binary accelerator system based on cyclohexyl benzothiazole sulfenamide (CBS), tetramethyl thiuram di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
3
14
2
Order By: Relevance
“…This expression is: where C 1 and C 2 are constants characterizing the vulcanizates. However, Lawandy and Halim14 showed that at strain values less than 16%, the parameter C 2 tends to be zero.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This expression is: where C 1 and C 2 are constants characterizing the vulcanizates. However, Lawandy and Halim14 showed that at strain values less than 16%, the parameter C 2 tends to be zero.…”
Section: Resultsmentioning
confidence: 99%
“…The ultrasonic technique was successfully used as a tool to investigate many polymeric properties. [11][12][13] However, in our previous work, 14 the crosslink density of various nitrile mixes was calculated using the kinetic theory of elasticity. In this study, we are trying to calculate the crosslink density of SBR vulcanizates, containing different vulcanizing system, by stressstrain measurements and ultrasonic technique.…”
Section: Introductionmentioning
confidence: 99%
“…Thiurams can be used for a wide range of sulfur accelerator ratio [108] . Combination of thiurams as a secondary accelerator with rapid accelerators such as xanthate and dithiocarbamate, imparts a retarding effect without affecting the crosslink density of the vulcanizate, whereas the curing rate is enhanced with an accelerator such as thiazole [109] .…”
Section: Modifi Ed Sulfur Vulcanization Systemsmentioning
confidence: 99%
“…During dynamic vulcanization, the rubber phases are finely dispersed to the mean particle size of a few microns through intense mixing and then are cross-linked with each other. Usually, the vulcanization is achieved by covalent bondings, such as sulfur crosslinking and carbon crosslinking [6,7]. However, there are still some problems which need to be solved to improve the rubber properties.…”
Section: Introductionmentioning
confidence: 99%